A 20 days visual follow up on Herpes zoster (shingles): Diagnosis, treatment and clinical outcome - Aghdaee, AmirHossein; Hashemi, Seyed Mahmoud (Student Research in Translational Medicine, 2023)
A 44-year-old man with a three-day history of pain in right axilla, subsequently accompanied by the appearance of vesiculopapular rashes on the right portion of his torso, attended a medical facility. The patient had neither reported any special skin contact in that area, nor fever and other symptoms. Upon examination, the examiner revealed the appearance of some other similar vesiculopapular rashes. These two affected sites were located in a linear arrangement, namely, the T7 dermatome. Considering the particular arrangement of rashes and form of manifestation, a clinical diagnosis of herpes zoster was made. The patient underwent empirical treatment of herpes zoster, including Virabex (valaciclovir) tablet 1g TDS, pregabalin capsule once nightly, and hydroxyzine hydrochloride tablet once every night. The pain and itching resolved within one week after the prescription, and the rashes mostly disappeared within 20 days. Here, the daily state of rashes are presented to the audience.